Synthesis and Cytotoxicity of 28a‐Homothiolupanes and 28a‐Homothiolupane Saponins. Issue 2 (25th November 2015) - Sidoryk, Katarzyna; Korda, Anna; Rárová, Lucie; Oklešťková, Jana; Pakulski, Zbigniew; Strnad, Miroslav; Cmoch, Piotr; Gwardiak, Katarzyna; Karczewski, Romuald
Abstract: A concise synthesis of 28a‐homo‐28a‐thiolupane triterpenes and the corresponding saponins containingD ‐mannose, D ‐idose, L ‐arabinose andL ‐rhamnose moieties was elaborated. New triterpenes were obtained from readily available 3‐ O ‐allylbetulinal by elongation of the carbon chain by Wittig reaction, followed by hydrolysis of the enol ether, reduction of the elongated aldehyde and nucleophilic substitution of the corresponding mesylate with thiocyanate ion. Saponins were obtained by glycosylation of triterpenes with classical Schmidt donors. The cytotoxic activities of the new homothiolupane compounds were evaluated in vitro, revealing that some triterpenes and the corresponding saponins exhibited interesting cytotoxic activity profiles against human cancer cell lines. An unexpected influence of the allyl protecting group on the cytotoxicity of homothiobetulin derivatives was revealed. These results open the way to the synthesis of various lupane‐type derivatives containing sulfur in the lupane side chain as potential anticancer compounds. Abstract : Homothiolupane‐type triterpenes have been synthesized by elongation of the carbon chain followed by nucleophilic substitution with thiocyanate ion. The corresponding saponins were obtained by glycosylation of homothiobetulin. Cytotoxic activities were evaluated in vitro. The influence of the allyl protecting group on the cytotoxicity is discussed.